X linked agammaglobulinaemia with a 'leaky' phenotype. Issue 6 (June 1996) - Jones, A; Bradley, L; Alterman, L; Tarlow, M; Thompson, R; Kinnon, C; Morgan, G
Abstract : Typical X linked agammaglobulinaemia (XLA) is characterised by absence of immunoglobulin production and lack of mature B cells. The gene responsible for XLA has recently been identified, and codes for a B cell tyrosine kinase, BTK. A family affected by a B cell immunodeficiency, which is less severe than classical XLA, is described but they had a pedigree suggestive of X linked inheritance. Demonstration of a mutation in the BTK gene confirms that this is a mild form of XLA.